Totally opportunistic routing algorithm for underwater wireless sensor network - Rahman, Ziaur (2019)
Underwater wireless sensor network (UWSN) is the enabling technology for a new era of underwater monitoring and actuation applications. Although acoustic communication has been investigated for decades, however, that mainly focuses on the physical layer and its related issues like low bandwidth and considerable propagation delay. Apart from physical layer issues, nodes localization, data aggregation, and forwarding are also intensely constrained due to channel impairment and which needs due consideration. Until now, the scientific community has yet to investigate the principles that will usher the design of networking protocols for UWSN. It is due to the fact that the protocols designed for terrestrial wireless sensor net- works cannot be applied for a UWSN since it uses the acoustic channel instead of a radio-frequency-based channel. This dissertation addresses the problem of nodes localization, real-time data delivery, and void node issue in three-dimensional UWSN. This thesis investigates the localization problem in large scale UWSN and proposes a hierarchical localization scheme. The proposed scheme performs its operation in two stages: anchor node localization and ordinary node localization. The former can be localized by utilizing any of the existing schemes, whereas for the later a Time of Arrival (ToA) based distributed 3-dimensional Euclidean distance estimation method has proposed. Opportunistic Routing (OR) is an advanced technique that can improve the data collection process of a wireless network, spesifically the acoustic network. This thesis stipulates a general discussion for high-delity and energy-efficient data collection in UWSN. In the first part of the thesis, the symbiotic design of opportunistic routing protocols for UWSN is given in detail. In the second part, a new localization scheme for underwater wireless sensor network has been proposed. In the third part, TORA and NA-TORA have been presented, which are energy efficient and opportunistic routing protocols that rely on node position information for data transmission to ensure packet delivery. In TORA next-hop forwarder is selected on the y, where the designated next-hop forwarder is selected based on its distance from the sink node. Whereas in NA-TORA, Expected Transmission Count (ETX) and residual energy of a node are considered for data transmission to ensure packet delivery. The suggested data forwarding algorithms are designed to abstain horizontal transmission, to lower end to end delay and improve throughput and energy efficiency. In the fourth and final part, a void detection and avoidance based routing protocol called NA-TORA with VA has been presented. The unreliable communication environment of UWSN and the existence of a void node in the routing path improves the chances of not receiving data on the designated next-hop forwarder. Avoiding void nodes in the data forwarding route is quite a challenging task in UWSN due to node mobility and three-dimensional localization. In such cases selecting next-hop forwarder on the y is one of the solutions, which has been adopted by the proposed opportunistic routing protocols. An extended version of NA-TORA called NA-TORA with VA has been proposed to overcome the problem of void nodes in the data forwarding route by utilizing the angle of transmission adjustment and transmission range extension method. Comprehensive and extensive simulations were performed to assess the performance of the proposed schemes for high network traffic load under widely spaced and very dense network scenarios. Simulation results show that NA-TORA significantly improves the network performance when compared to some relevant existing routing protocols, such as VBF, HH-VBF, and TORA, for energy consumption, average end-to-end delay, and packet delivery ratio. NA-TORA reduces energy consumption by an average of 44% of VBF, 49% of HH-VBF, and 9% of TORA, whereas the average end-to-end delay has been reduced by 80% of VBF, 79% of HH-VBF, and 10% of TORA. Moreover, the packet delivery ratio has been improved by an average of 51% of VBF, 34% of HH-VBF, and 8% of TORA.